Strategic Steps To Prevent COVID 19 Pendemi At the Indonesian Correctional Institution - hidayat, risyal hardiyanto (Jurnal Pendidikan Kesehatan, 2020)
All countries are currently feeling the Covid 19 epidemic which makes all of the community anxious and vigilant regarding the spread of this virus, it is also felt by Penitentiary Citizens in the Penitentiary in the midst of their overcrowding overcrowding conditions, seeing the situation then the need for strategic steps and policies that must be taken. The purpose of this research is to find out the steps taken by the Ministry of Law and Human Rights in preventing Covid 19 in the midst of the present condition of Corrections Institutions. The method used in this study is a qualitative method. Data collection techniques using literature study and in depth interviews. The results showed that the Ministry of Law and Human Rights had taken steps to prevent Covid 19 in Penitentiary through ministerial decrees such as WFH, implementation of strict health protocols, delays, transfer of prisoners and the use of video conferences in the online trial system and prisoner release programs through assimilation and integration rights